2012
DOI: 10.1097/jto.0b013e3182397751
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Long-Term Survival and Cure Rates in Esophageal Cancer: A SEER Database Analysis

Abstract: Long-term survival with esophageal cancer is poor but survival of local esophageal cancer improved dramatically over the decades. Complete cure of nonmetastatic esophageal cancer seems possible in a growing number of patients. Early diagnosis and treatment are crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
145
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(158 citation statements)
references
References 16 publications
4
145
1
1
Order By: Relevance
“…Due to the improvement of endoscopy and staining methods, the detection rate of EEC in our hospital rose significantly in the past five years, and reached to nearly 10%. But the detection rate is still lower than that of 15%-30% in Japan and western countries (Natsugoe et al, 2004;Stein et al, 2005;Saha et al, 2009;Bogoevski et al, 2011;Dubecz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the improvement of endoscopy and staining methods, the detection rate of EEC in our hospital rose significantly in the past five years, and reached to nearly 10%. But the detection rate is still lower than that of 15%-30% in Japan and western countries (Natsugoe et al, 2004;Stein et al, 2005;Saha et al, 2009;Bogoevski et al, 2011;Dubecz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several individual studies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)27) and 2 systematic reviews (that produced essentially identical results despite slightly different methodologies (16,17)) have reported that statin use, and particularly statin use combined with a cyclo-oxygenase inhibitor, is associated with a reduced incidence of esophageal adenocarcinoma. This has been reported in cohort studies and case-control studies of Barrett's patients and population-based studies compared to population-based controls, although not all studies are in agreement (28).…”
Section: Discussionmentioning
confidence: 99%
“…It is accepted that metaplastic transformation of the esophageal squamous mucosa to intestinaltype mucosa (Barrett's esophagus (BE)) is a premalignant phenotype, although the overall rate of progression is relatively low (probably about 1 in 300 patients per year, or less) (5)(6)(7) and this has allowed the development of surveillance and localised treatment strategies such as radio-frequency ablation as means of preventing the development of EAC (8). However overall mortality from EAC remains considerable with 5-year survival less than 25% (9).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 3 decades, surgical advances and improvement in radiation techniques have greatly improved the disease outcomes. [9][10][11] This article focuses on integrating these approaches and tailoring the treatment strategy for individual patients, compares the effectiveness of the various treatment approaches in the definitive or neoadjuvant…”
Section: Introductionmentioning
confidence: 99%